Analisis Pelaksanaan Program Kemitraan Bidan dan Dukun Ditinjau Dari Aspek Input, Proses dan Output di Wilayah Dinas Kesehatan Kabupaten Fakfak Provinsi Papua Barat - Elzina De Fretes; Hardi Warsono; Ayun Sriatmi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
Number of midwives in Fakfak District in 2012 was 108 persons. Number of Traditional Birth Attendants (TBAs) was 191 persons consisted of 79 (41%) trained TBAs and 112 (59%) untrained TBAs. The TBAs had an important role in delivery process because number of them was higher than number of midwives. Therefore, coverage of delivery process helped by health workers had not achieved the target. This research aimed to analyze the implementation of the partnership program between midwives and TBAs viewed from the aspects of input, process, and output at Fakfak District Health Office. This was qualitative research with descriptive-explorative approach by conducting indepth interview. Subjects were midwives and TBAs who had been partnering. Data were analysed using a content analysis. The input aspect showed that: 1) Implementers, midwives and TBAs only knew partnership in helping delivery; 2) Specific allocation funds for the program was not available. The funds was from Operational Support for Health but it was still not sufficient; 3) Specific means for the program was not available. The current means is from health center and village polyclinic but it is still limited. Furthermore, the process aspect revealed that: 1) Program planning, midwives and TBAs collected data of pregnant women, maternal, postpartum women, and number of TBAs; 2) The implementation was not good because midwives were not available when needed by TBAs and there was difficult to access. Socialization for cross-program (community leaders and religious leaders) and internship for TBAs had not been done yet due to insufficient fund; 3) Recording and reporting especially about partnership activities had not been done yet and only used a form on a Maternal and Child Health report. Regarding the output aspect, as many as 195 (89%) from 219 TBAs had not been partnered. Coverage of K1, K4, and delivery process helped by health workers from 2011 to 2012 decreased gradually. As a suggestion, District Health Office and Health Center need to maintain partnership by recruiting midwives, providing means, allocating fund, socializing to community leaders, and funding TBAs’ daughter or grandchild to study midwifery.